Does endoscopic sinus surgery alter the biomechanics of the orbit? - Leigh J Sowerby; Matthew S. Harris; Rootu Joshi; Marjorie Johnson; Tom Jenkyn; Corey C. Moore (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective The purpose of this study is to determine if removal of ethmoid cell septations as commonly performed in endoscopic sinus surgery leads to a change in orbital wall fracture patterns and the force required to create them. Methods Six fresh-frozen cadaveric heads were acquired and underwent endoscopic uncinectomy, maxillary antrostomy, and anterior and posterior ethmoidectomy on one, randomized, side. The contralateral sinuses were used as intra-specimen control. Hyaluronic acid gel globe injections were performed to simulate normal intra-ocular pressure. Post-op CT scans confirmed no orbital fractures or violation of the lamina papyracea prior to trauma testing. Orbital trauma was induced using a guided weight-drop technique. Both orbits were tested in random order, and sequentially higher drops were performed until both the test and control side demonstrated an orbital fracture on CT scan. Results In all six heads, the post-sinus surgery side incurred a medial orbital wall fracture, and no orbital floor fractures were identified. On the other hand, on the control side, all six heads incurred orbital floor fractures at drop heights equal to, or higher than, the surgical side. Fisher’s exact test demonstrated a significant difference in fracture pattern (p <  0.001). Conclusions To our knowledge, this is the first demonstration that the structures removed during sinus surgery may act as a buttress for the medial orbital wall. The anatomic changes of sinus surgery may alter the biomechanics of the orbit and affect the pattern of subsequent traumatic blowout fractures.